LO42: A systematic review of short-term use of therapeutic opioids for children and future opioid use disorders. (May 2020) - Ali, S.; Afzalzada-Ahrari, M.; Dyson, M.; DaRosa, D.; Dong, K.; Drendel, A.; Hartling, L.
Abstract : Introduction: Despite an overall decline in opioid prescriptions in Canada, healthcare visits, hospitalizations, and deaths due to opioid-related harms continue to rise for children. Clinicians urgently require high quality synthesized evidence to inform personalized decisions regarding opioid use for children. The objective of this systematic review was to examine the association between short-term therapeutic exposure to opioids and development of opioid use disorder. Methods: A medical librarian conducted a comprehensive search of 10 databases from inception to May 2019. Two authors independently assessed studies for inclusion. Studies were eligible if they reported primary research in English or French, and study participants had short (<14 days) or non-specific duration of therapeutic exposure to opioids before age 18 years. Primary outcome was the development of an opioid use disorder; secondary outcomes included opioid addiction, dependence, misuse, and abuse. Data extraction involved two independent reviewers utilizing a standardized form. Methodological quality was assessed using the NIH tools for observational studies. Results are described narratively. Results: The search identified 4, 072 unique citations; 82 were selected for review, and 17 were included (3 retrospective cohort, 4 prospective cohort, and 10 cross-sectional). All studies took place in the USA. A total of 1, 562, 503 participants were analyzed. Nine studies were administered in schools, 3 used administrative data. While most settings were non-specific, 1 study examined opioid use in dentistry, 1 in trauma, and 1 in organized sports. One comparative study showed an association between short-term therapeutic use and opioid misuse. Two studies showed opioid related adverse events (e.g., overdose) among cohorts exposed to short-term use. The remaining 14 studies did not specify duration of exposure; therefore, confirming whether misuse was due to short-term therapeutic exposure was not possible. Conclusion: A small number of studies in this review suggest an association between short-term opioid use and opioid misuse; however, further analysis is underway with consideration of methodological limitations of the individual studies (final results pending). Careful consideration of the risk and benefits of short-term opioid use should be undertaken prior to prescribing opioids. PROSPERO Registration Number: 122681.